O028 Multi-centre UK analysis after simultaneous pancreas and kidney transplantation in recipients with type 2 diabetes mellitus. (22nd July 2022) - Owen, RV; Carr, HJ; Counter, C; Thompson, EJ; Shaw, JA; Wilson, CH; White, SA
Abstract: Introduction: Only 3.4% of simultaneous pancreas and kidney transplants (SPKT) in the UK are performed for recipients with T2DM. The aim of this study was to compare outcomes after SPKT for recipients with either T1DM or T2DM. Methods: Data on all UK SPKTs from 2003–2019 were obtained from the NHSBT UK Transplant Registry (n=2, 236). Current SPKT selection criteria for T2DM requires insulin treatment and recipient BMI<30kg/m2 at listing. Cases where the aetiology of diabetes was missing and recipients who had received a re-transplant were excluded, resulting in a final cohort of n=2, 154. Graft (GS) and patient (PS) survival analyses were conducted using Kaplan-Meier plots and Cox regression models. Complications were compared using chi-squared analyses. Results: The majority of SPKTs were performed in recipients with T1DM (95.6%, n=2, 060), and 3.4% (n=94) were performed in T2DM recipients. Recipients with T2DM were statistically significantly more likely to be older (p<0.0001), male (p<0.0001), with a higher BMI (p=0.0191), and not requiring dialysis (p<0.0001). Univariate analysis showed comparable outcomes for GS and PS at 1yr (GS p=0.120; PS p=0.886) and 3yrs (GS p=0.316; PS p=0.237). Multi-variate analysis also showed comparable outcomes in GS (p=0.564, HR 1.221, 95%CI 0.619, 2.406) and PS (p=0.556, HR 1.280, 95%CI 0.563, 2.911). Common complications after SPKT were analysed and no statistically significant differences were seen between recipients. Conclusion: This is the largest European study evaluating outcomes after SPKT comparing recipients with T1DM or T2DM. Carefully selected recipients with T2DM were shown to have comparable graft survival, patient survival and rates of complications. Take-home message: Carefully selected recipients with T2DM were shown to have comparable graft survival, patient survival and rates of complications.